Determination of anabolic steroids by gas chromatography negative-ion chemical ionization mass spectrometry and gas chromatography negative-ion chemical ionization tandem mass spectrometry with heptafluorobutyric anhydride derivatization - Choi, MH; Chung, BC; Lee, W; Lee, UC; Kim, Y (JOHN WILEY & SONS LTD, 1999)
A gas chromatography/mass spectrometry (GC/MS) method is described which uses negative ion chemical ionization (NCI) and tandem mass spectrometry (MS/MS) for the determination of eight anabolic steroids in human urine. Eight anabolic steroids were derivatized by heptafluorobutyric anhydride (HFBA), and were determined using GC/NCI-MS and GC/NCI-MS/MS. The linear correlation coefficients for calibration in NCI-MS/MS were in the range 0.9880-0.9988, This method of derivatization with HFBA for use with GC/NCI was useful in determinations of 19-norandrosterone, boldenone, 19-noretiocholanolone, 2-methylandrosterone, nandrolone, 1-methyleneandrosterone, 1-methylandrosterone, 4-dihydroboldenone and mesterolone, The detection limits of this procedure were 5-20 ppb at a signal-to-noise (S/N) ratio of 3, Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: INTERFERENCES; CONFIRMATION; SUBSTANCES; URINE; DRUGS